On the Fourier transformation of the Hamming norm - Chernov , N. G. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Let λ ε ℕ U {0} and let H be the Hamming norm on the linear space Fnq over the finite field Fq. The Fourier transform of degree λ of the norm H is investigated. The result is applied to the description of the Riemann—Liouville operator in the space of ℂ-valued functions on the space Fnq.